2023
DOI: 10.1172/jci.insight.167211
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar repair following LPS-induced injury requires cell-ECM interactions

Abstract: During alveolar repair, alveolar type 2 (AT2) epithelial cell progenitors rapidly proliferate and differentiate into flat AT1 epithelial cells. Failure of normal alveolar repair mechanisms can lead to loss of alveolar structure (emphysema) or development of fibrosis, depending on the type and severity of injury. To test if β 1 -containing integrins are required during repair following acute injury, we administered E . coli lipopolysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…While previous studies have not directly characterized the impact of ECM proteins on iAT2s, studies employing iAT2-fibroblast co-cultures have demonstrated using single-cell RNA sequencing that fibroblasts actively express ECM genes concurrent with the emergence of transitional cell state and AT1-like subpopulations of iAT2s, suggesting a potential role of ECM in iAT2 differentiation 25 , 26 . Further, a recent study has demonstrated the role of ECM-binding through β1-integrin as an important process in AT2 morphological and transcriptional differentiation 9 . Within this study, a mouse model of β1-integrin null AT2s found that, following injury to the alveolar epithelium, AT2 differentiation into elongated squamous AT1s was significantly inhibited 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While previous studies have not directly characterized the impact of ECM proteins on iAT2s, studies employing iAT2-fibroblast co-cultures have demonstrated using single-cell RNA sequencing that fibroblasts actively express ECM genes concurrent with the emergence of transitional cell state and AT1-like subpopulations of iAT2s, suggesting a potential role of ECM in iAT2 differentiation 25 , 26 . Further, a recent study has demonstrated the role of ECM-binding through β1-integrin as an important process in AT2 morphological and transcriptional differentiation 9 . Within this study, a mouse model of β1-integrin null AT2s found that, following injury to the alveolar epithelium, AT2 differentiation into elongated squamous AT1s was significantly inhibited 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent study has demonstrated the role of ECM-binding through β1-integrin as an important process in AT2 morphological and transcriptional differentiation 9 . Within this study, a mouse model of β1-integrin null AT2s found that, following injury to the alveolar epithelium, AT2 differentiation into elongated squamous AT1s was significantly inhibited 9 . This resulted in the accumulation of enlarged, round AT2s with transitional cell state genetic markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AT2 cell differentiation to AT1 cells is regulated by the Notch, Hedgehog, and Wnt signaling pathways. In addition, the AT2 cell progenitor gains an AT2-to-AT1 transitional cell state expressing KRT8, HBEGF, or AREG genes [52]. Any deficiencies in surfactant protein impair normal lung functions [53].…”
Section: Lung Microenvironmentmentioning
confidence: 99%